1990
DOI: 10.1103/physrevb.42.8768
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of the systemLa2xSr

Abstract: The electronic structure of La2-Sr Cu04+~has been studied by measuring 0 1s absorption edges using high-energy electron-energy-loss spectroscopy in transmission.Upon doping the insulating compound the conduction-band states are reduced and states in the gap are formed. When going from insulating to conducting compounds there is a continuous increase of states at the Fermi level, which is at the bottom of the gap. The insulator-metal transition is probably driven by delocalization of these states.Among the cupr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(78 citation statements)
references
References 17 publications
9
68
1
Order By: Relevance
“…The focus of these studies on the La 2-x Sr x CuO 4 (LSCO)-system was the underdoped range, where effects due to the pseudogap and the spectral weight renormalization were discussed for the occupied DOS. Interestingly in the overdoped range the DOS at E F was found to converge to a constant value and a similar trend was observed by Romberg et al [4] for the unfilled DOS by EELS. Although the authors did not explicitly comment on this, in a naive view one would expect an increasing DOS with increasing hole concentration.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…The focus of these studies on the La 2-x Sr x CuO 4 (LSCO)-system was the underdoped range, where effects due to the pseudogap and the spectral weight renormalization were discussed for the occupied DOS. Interestingly in the overdoped range the DOS at E F was found to converge to a constant value and a similar trend was observed by Romberg et al [4] for the unfilled DOS by EELS. Although the authors did not explicitly comment on this, in a naive view one would expect an increasing DOS with increasing hole concentration.…”
Section: Introductionsupporting
confidence: 67%
“…It is established that the states at the Fermi energy have primarily O 2p-character [17] and are connected with the prepeak feature of the O 1s → 2p absorption edge. The intensity of the prepeak is mainly interpreted as a direct measure of the hole concentration [4]. In contradiction to this assumption there are hints already in this previous experiment [4] which will be confirmed here by a large number of measured samples that for hole overdoping the intensity of the prepeak is not further increasing but saturating.…”
Section: Introductionmentioning
confidence: 37%
See 1 more Smart Citation
“…Peak A is due to the transition from the O 1s levels into the unoccupied O 2p states appearing in the correlation gap with doping holes and has been observed for a number of correlated systems [29]. It has been found that the intensity of this peak is not explicitly dependent on the T c of the material but is dependent on the density of the doping holes [30,31]. The intensity of peak A decreases in going towards the E c polarization.…”
Section: O K-edge Xas Measurementsmentioning
confidence: 99%
“…First, the structure of doped cuprates has been found to be essentially inhomogeneous on the nanoscale (stripes, tweed patterns, granularity) with the associated electronic phase separation [6][7][8][9][10][11][12] in the CuO 2 planes. At the same time it has been found that the hole doping creates a new band of defect-states in the cuprate charge-transfer gap [13][14][15][16][17][18][19][20][21][22][23][24]. Various data have indicated the functioning of itinerant and "defect"-type carriers in the basic physics of cuprate superconductivity.…”
Section: Introductionmentioning
confidence: 99%